2015
DOI: 10.1124/jpet.115.229369
|View full text |Cite
|
Sign up to set email alerts
|

Notoginsenoside Ft1 Promotes Fibroblast Proliferation via PI3K/Akt/mTOR Signaling Pathway and Benefits Wound Healing in Genetically Diabetic Mice

Abstract: Wound healing requires the essential participation of fibroblasts, which is impaired in diabetic foot ulcers (DFU). Notoginsenoside Ft1 (Ft1), a saponin from Panax notoginseng, can enhance platelet aggregation by activating signaling network mediated through P 2 Y 12 and induce proliferation, migration, and tube formation in cultured human umbilical vein endothelial cells. However, whether it can accelerate fibroblast proliferation and benefit wound healing, especially DFU, has not been elucidated. In the pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
41
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(43 citation statements)
references
References 32 publications
2
41
0
Order By: Relevance
“…An earlier study reported that PNS alters the activity of PI3K/AKT signaling pathway molecules, and then regulated the cell proliferation and apoptosis (23). In the current study, the results indicated that nerve cells stimulated with sevoflurane had significantly decreased phosphorylation of AKT.…”
Section: Discussionsupporting
confidence: 58%
“…An earlier study reported that PNS alters the activity of PI3K/AKT signaling pathway molecules, and then regulated the cell proliferation and apoptosis (23). In the current study, the results indicated that nerve cells stimulated with sevoflurane had significantly decreased phosphorylation of AKT.…”
Section: Discussionsupporting
confidence: 58%
“…The activation of the PI3K/Akt signaling pathway is coupled with regulating the proliferation of various cells [38][39][40]. The PI3K/Akt signaling pathway has effects on regulating mammary gland development [41,42].…”
Section: Discussionmentioning
confidence: 99%
“…Previously, it was reported that PNS promote wound repair of anterior cruciate ligament through phosphorylation of PI3K, AKT and ERK (Yu et al, 2015), promote osteogenic differentiation of bone marrow stromal cells through the ERK and P38 MAPK (Linares and Gisbert, 2011), and activate PI3K/Akt pathway in cardiomyocytes (Chen et al, 2011). In addition, Its effective components Notoginsenoside R1-mediated neuroprotection through estrogen receptor-dependent crosstalk between Akt and ERK1/2 pathways (Meng et al, 2014), while Notoginsenoside Ft1 promotes fibroblast proliferation via PI3K/Akt/mTOR signaling pathway (Zhang et al, 2015b). Those above results suggested that PNS stimulate ERK, PI3K and P38MAPK signaling pathway to exert biological activity.…”
Section: Discussionmentioning
confidence: 99%